Analysis of Hydrological Memory Characteristics in Taiwan’s Catchments - Ting-Jui Fang; Hsin-Yu Chen; Hsin-Fu Yeh (Atmosphere)
Climate change often affects streamflow, which can be categorized into immediate and lag responses. Historically, the phenomenon of lag responses, known as hydrological memory, has often been overlooked. This study aims to determine whether hydrological memory characteristics exist in Taiwan’s catchments and to identify the lag time in streamflow response. Using data from 67 catchments across Taiwan with a length of over 30 years, the study examines the response of streamflow to precipitation and potential evapotranspiration across different time scales. Streamflow elasticity was employed to quantify the sensitivity of catchment streamflow. Sensitivity analysis results indicate that the month scale better explains the sensitivity of streamflow to climatic factors compared to the year scale. Therefore, memory characteristics are discussed using the month scale. Only 19.4% of the studied catchments exhibit significant hydrological memory, making it a rare phenomenon in Taiwan. The conceptual model of hydrological memory shows that extreme precipitation and other hydrological climate anomalies primarily impact river streamflow generation 33 days (1.11 months) later, with the influence of precipitation on streamflow recharge lag up to 50 days (1.67 months). Catchments with hydrological memory characteristics are predominantly located in southwestern Taiwan, mainly in catchments smaller than 500 km2, with generally lower baseflow indices and a higher proportion of streamflow contributions. These characteristics are less common in high-elevation areas. The results of this study highlight that streamflow response to climatic factors exhibits a lag time, illustrating the memory characteristics of Taiwan’s catchments. This understanding will aid in the prediction of hydrological phenomena and provide valuable references for hydrological modeling and the development and management of water resources.